Novel ferrocenic steroidal drug derivatives and their bioactivities - Manosroi J. (2014)
Seven novel ferrocenic derivatives, compounds 1-7, were synthesized from steroidal drugs by Aldol condensation reaction. The derivatives were purified by chromatography, and their structures were determined on the basis of HR-ESI-MS and two-dimensional NMR spectroscopy. The purity of all derivatives was more than 95%. Compounds 1-5 demonstrated anti-proliferative activity on HeLa cell line by SRB assay more than their parent compounds. All seven derivatives showed anti-oxidative activities evaluated by DPPH scavenging and metal ion chelating, while their parent compounds gave no activity. Compound 1 indicated the most potent anti-proliferative activity similar to doxorubicin, with the GI 50 at 0.223 ± 0.014 μg/mL. Compounds 6 and 7 demonstrated similar potent in vivo anti-inflammatory to their parent compounds (prednisolone and hydrocortisone) at 80.99 ± 13.5 and 68.24 ± 10.4% edema inhibition, respectively. This study has suggested that the novel compound 1 was the most potential derivative that can be further developed for cancer treatment. © 2010 American Chemical Society.